Population benefits of addressing programmatic and social determinants of gender disparities in tuberculosis in Viet Nam: A modelling study. - Katherine C Horton; Richard G White; Nguyen Binh Hoa; Hai Viet Nguyen; Roel Bakker; Tom Sumner; Elizabeth L Corbett; Rein M G J Houben (Public Library of Science (PLoS), 2022)
High prevalence of infectious tuberculosis among men suggests potential population-wide benefits from addressing programmatic and social determinants of gender disparities. Utilising a sex-stratified compartmental transmission model calibrated to tuberculosis burden estimates for Viet Nam, we modelled interventions to increase active case finding, to reduce tobacco smoking, and to reduce alcohol consumption by 2025 in line with national and global targets. For each intervention, we examined scenarios differentially targeting men and women and evaluated impact on tuberculosis morbidity and mortality in men, women, and children in 2035. Active case finding interventions targeting men projected greater reductions in tuberculosis incidence in men, women, and children (16.2%, uncertainty interval, UI, 11.4-23.0%, 11.8%, UI 8.0-18.6%, and 21.5%, UI 16.9-28.5%, respectively) than those targeting women (5.2%, UI 3.8-7.1%, 5.4%, UI 3.9-7.3%, and 8.6%, UI 6.9-10.7%, respectively). Projected reductions in tuberculosis incidence for interventions to reduce male tobacco smoking and alcohol consumption were greatest for men (17.4%, UI 11.8-24.7%, and 11.0%, UI 5.4-19.4%, respectively), but still substantial for women (6.9%, UI 3.8-12.5%, and 4.4%, UI 1.9-10.6%, respectively) and children (12.7%, UI 8.4-19.0%, and 8.0%, UI 3.9-15.0%, respectively). Comparable interventions targeting women projected limited impact, with declines of 0.3% (UI 0.2%-0.3%) and 0.1% (UI 0.0%-0.1%), respectively. Addressing programmatic and social determinants of men's tuberculosis burden has population-wide benefits. Future interventions to increase active case finding, to reduce tobacco smoking, and to reduce harmful alcohol consumption, whilst not ignoring women, should focus on men to most effectively reduce tuberculosis morbidity and mortality in men, women, and children.